Pendidikan Agama Islam Dalam Kurikulum Nasional - Indra Taupik Saleh; Deni Sopiansyah; Uus Ruswandi (Jurnal Dirosah Islamiyah, 2022)
This article aims to determine the purpose of Islamic Religious Education in the National Curriculum. The research method in this writing uses qualitative methods, namely by means of library research, searching and collecting from various relevant sources. The results of this study indicate that Islamic Religious Education has been running since before independence. Then develop and systematically designed and structured which is then formed in a curriculum. The Islamic Religious Education in the National Curriculum follows the changes that the government has made, namely adjusting the content of its learning to the needs of the 21st century, namely the existence of 4 C's. Keywords: education, Islamic religion, national curriculum.